KARAKTERISTIK PENDERITA STROKE HEMORAGIK (SH) RAWAT INAP DI RSUD RADEN MATTAHER PROVINSI JAMBI TAHUN 2015 - ira aminah padang; Rasmaliah .; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Abstract Stroke is the third most common non-communicable diseases and the highest cause of disability in the world. There are two types of stroke by pathological processes that ischemic stroke and hemorrhagic stroke. According to AHA, the mortality rate of stroke patients each year are 50-100 of 100,000 patients. Based on Batubara’s research of acute stroke patients in RSUP HAM Medan January to Desember 2011 kind of stroke that causes the most deaths is 87.5% hemorrhagic stroke. This research is descriptive study using case series design. The population is 127 data of patient with total sampling. The Result of this research is founded the highest proportion of stroke hemorrhagic patient based on age of 40-69 years is 66.1%, male 57.5%, Islam 81.9%, civil servant 30.7%, married 81.9%, lived in Jambi city 59.8%, history of diseases hypertention 59.4%, disorder of speech and movement 32.23%, sistolic pressure hypertention 92.9%, diastolic pressure hypertention 93.7%, uncertain DM 73.2%, total cholesterol border 40.2%, normal triglyceride level 64.6%, normal LDL and border LDL 35.4%, normal HDL 46.5%, hemisphere dextra 49.6%, CT-Scan result with bleeding of Intra Cerebral 69.3%, location bleeding in Hemisphere/Lobar 36,2%, managed by conservative 97.6%. average lenght of stay 5.88 (6 days), source of finance from JKN 76.4%, no refferal 55.1%, died 64.6%. Found significant different between CT-Scan result by status of discharged (p=0,006) and between average length of stay by status discharged (p=0,0001). For hypertention patient with age 40-69 years were encouraged to have routine controlling and healthy lifestyle to prevent a stroke, for RSUD Raden Mattaher to increase the effort of promotive , curative , and rehabilitif to reduce the number of morbiditi and mortaliti caused by the hemorrhagic stroke, and for medical record department RSUD Raden Mattaher Province Jambi should have to complete the data such as ethnic and education. Keywords: Hemorrhagic stroke , Characteristics of patients hemorrhagic stroke